Shape optimisation (topology optimisation) using ANSYS Parametric Design Language (APDL) - Chew, Jun Jie (Nanyang Technological University, 2020)
With the proliferation of Additive Manufacturing (AM), Topology Optimisation (TO) has been garnering increased attention over its ability to generate light-weight structures that still fulfill its structural requirement. However, this function is currently unavailable in ANSYS Parametric Design Language (APDL), causing designers unable to perform optimisation while using the software in the design phase. This report shall explore the suitability of using APDL to perform TO and generate a program that can perform the stated function. A detailed literature review shall be performed first to offer readers with a basic understanding of TO. To reduce complexities, only 2D applications shall be focused in this report and the types of structure to be analysed consist of a block, plate and cantilever. Thereafter, optimisation will be performed on each structure before validation with ANSYS Workbench is done. Progressively, enhancement(s) of the program will be made to the extent that an automated program with minimal human intervention can be developed, relations between various factors (mesh size and stress threshold value) and the number of iterations can be assessed as well. Before ending the report, pointers on future work will be discussed in brief details to offer readers with a broad overview of the challenges ahead to create a robust, efficient TO program that is suitable across a wide range of applications in APDL.